Noble MXene nanofluids' impact on solar collector effectiveness enhancement: a CFD numerical evaluation - Farhana, Kaniz; Mahamude, Abu Shadate Faisal; Kadirgama, Kumaran; Rajan, Jose (Springer Nature, 2024)
The thermal flat plate solar collector (FPSC) is a versatile solar harvesting system that may be integrated into various designs and base fluids. This study presents a novel investigation of using nanofluids to transfer thermal energy in an FPSC system. Using the governing equations in CFD simulations, the performance of an FPSC is studied numerically. The base fluid has been defined as a 60:40 blend of ethylene glycol and water. The effects of three distinct volume fractions of MXene nanofluids in the 0.01–0.1% range on the efficiency are investigated. The numerical findings revealed that employing MXene nanofluid increases outlet temperature efficiency by about 5.83%, 6.06%, and 6.31% when 0.01%, 0.05%, and 0.1% volume fractions of nanofluids are used, respectively. The research aims to create a validated numerical model that can be used to assess the effectiveness of FPSC utilizing ethylene glycol and water or other nanofluids of any mass fraction as a working fluid. To examine the overall effectiveness of the FPSC, a numerical model was created using Solidworks software and ANSYS ICEM CFD. The numerical findings revealed that (i) increasing the proportion of MXene nanofluid in the FPCS enhances efficiency to 0.1% volume fraction, and (ii) MXene nanoparticles may be used in the solar collector to improve efficiency.